How does market competition affect shareholder voting? Evidence from branching deregulation in the U.S. banking market - Karel Hrazdil; Jeong-Bon Kim; Lijing Tong; Min Zhang (Journal of Risk and Financial Management, 2022)
Exploiting interstate branching deregulations during 1994-2005 as exogenous shocks to banking market competition, we examine the impact of increased market competition on shareholder voting in the U.S. banking industry. Voting is one of the primary mechanisms through which shareholders participate in corporate governance and "voice" their opinions to company management, yet little is known about how external market environments shape shareholder voting behavior. Using a difference-in-differences design, and a sample of 596 banks (17,783 bank-year proposals), we are the first to provide large-sample, systematic evidence that the intensification of market competition leads to an increase in rates of disapproval for management proposals. We further document that the relation between the two is more pronounced among states with higher degrees of deregulation and weaker levels of pre-deregulation competition. Overall, our findings are consistent with the notion that increased competition among U.S. banks induces more shareholders to vote against management proposals.
Keywords: 650; bank deregulation; competitive pressure; market competition; shareholder voting